Emotional labor among team members: do employees follow emotional display norms for teams, not for customers? - Hong, DaEun; Kim, MinSoo (Frontiers in Psychology, 2023)
Emotional labor is typically conceptualized as a process in which individuals regulate their emotions in response to display rules. Most research on emotional labor has focused on the influence of display rules as individual-level perceptions, but rarely examined as team-level. We examine the influence of the shared display rules in teams as emotional display norms. This study considers emotional dissonance as the difference between the positive emotional display norm at the team-level and positive emotion at the individual-level. To examine the purpose of this study, data was collected from leader-follower pairs within teams and based on a three-wave design. Thus, this study conducted a multi-level polynomial regression analysis and used the response surface methodology to interpret the incongruence effect. The results show that the incongruence effect of emotional dissonance is positively related to surface acting. In addition, the moderating effect of regulatory focus significantly strengthens the positive relationship between emotional dissonance and emotion regulation strategies. The results also show that surface acting strategy is negatively related to selfless OCB. These findings highlight that emotional display norms play an important role as the standard for emotional experience in team, and, especially with the moderating effect of self-regulatory focus, emotion regulation strategies affect the selfless OCB rating of observers.